FIRST RECORD OF Sprostoniella multitestis CHOWSKY et NAGIBINA, 1967 (MONOGENEA: CAPSALIDAE) FROM Platax teira AND P. orbicularis (PISCES: EPHIPPIDAE) FROM MARINE WATERS OF IRAQ - Suzan A. Al-Azizz; Khalidah S. Al-Niaeem; Hayder A. H. Al-Hasson (Basrah Journal of Veterinary Research)
During the period from January 2014 to the end of July 2014, a total of 21 fishes belongingto two species of the family Ephippidae (Platax teira and P. orbicularis) were captured fromIraqi marine waters, northwest Arab Gulf. The study revealed the existence of one species ofmonogenean, Sprostoniella multitestis from gills of both fish species. The record of S.multitestis in the present study is considered as the first record in the Iraqi territorial waters ofthe Arab Gulf and both P. teira and P. orbicularis are new host records for this parasite in theArab Gulf.